Anti-Inflammatory Activity of Pinus koraiensis Cone Bark Extracts Prepared by Micro-Wave Assisted Extraction - Kang, Sun-Ae (Prev Nutr Food Sci, 2016)
In this study, we compared the anti-inflammatory activity of Pinus koraiensis cone bark extracts prepared by conventional extraction and microwave-assisted extraction (MAE). Water extracts and 50% ethanol extracts prepared using MAE were applied to RAW 264.7 cell at 5, 10, 25, and 50 μg/mL of concentrations, and tested for cytoxicity. The group treated with 50 μg/mL of 50% ethanol extracts showed toxicity. In order to investigate the inhibition of nitric oxide (NO) production in RAW 264.7 cells, extracts of water and ethanol were treated with 5, 10, and 25 μg/mL concentrations. The inhibitory activity of water and 50% ethanol extracts groups were determined as 40% and 60% at 25 μg/mL concentration, respectively. We found concentration dependent decreases on inducible NO synthase. The inhibitory effect against forming inflammatory cytokines, prostaglandin E(2), tumor necrosis factor-α, interleukin (IL)-6, and IL-1β, was also superior in the 25 μg/mL treated group than the control group. According to these results, the water extracts and 50% ethanol extracts both inhibited inflammatory mediators by reducing the inflammatory response. Therefore, The MAE extracts of P. koraiensis cone bark can be developed as a functional ingredient with anti-inflammatory activity.